2021
DOI: 10.47836/pjtas.44.3.10
|View full text |Cite
|
Sign up to set email alerts
|

An Optimised TRIzol-based Protocol for the Improvement of RNA Extraction Yield of Tomato Stem

Abstract: One of the most common methods for purifying RNA is using TRIzol reagent because of its simplicity and economic feasibility. However, the drawback of this method is frequently the low quality of extracted RNA due to contaminants from the residue of phenol and guanidinium thiocyanate from the reagents. This study aimed to evaluate the improvement in the quality and concentration of RNA after the optimisation treatment. One-month-old tomato (Solanum lycopersicum) stem was used in this research. TRIzol or acid gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The TRIzol method is relatively easy and is economically feasible, but the drawback is that due to the presence of phenol and guanidinium isothiocyanate, a low quality of RNA is extracted. When the TRIzol (Invitrogen) process was optimized, it showed enhancement in RNA yield and purity of the tomato stem sample . Another example includes isolation of potato spindle tuber viroid RNA using TRIzol reagent with β-marceptanol .…”
Section: Conventional To State-of-the-art Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRIzol method is relatively easy and is economically feasible, but the drawback is that due to the presence of phenol and guanidinium isothiocyanate, a low quality of RNA is extracted. When the TRIzol (Invitrogen) process was optimized, it showed enhancement in RNA yield and purity of the tomato stem sample . Another example includes isolation of potato spindle tuber viroid RNA using TRIzol reagent with β-marceptanol .…”
Section: Conventional To State-of-the-art Extraction Methodsmentioning
confidence: 99%
“…When the TRIzol (Invitrogen) process was optimized, it showed enhancement in RNA yield and purity of the tomato stem sample. 27 Another example includes isolation of potato spindle tuber viroid RNA using TRIzol reagent with βmarceptanol. 28 Similarly, in the case of sweet potato feathery mottle virus affecting Chrysanthemum morifolium, TRIzol reagent was used to isolate RNA.…”
Section: Conventional To State-of-the-art Extraction Methodsmentioning
confidence: 99%
“…As averse to senescent sweetening (natural irreversible process occurring as a result of cellular breakdown due to tuber aging); cold-induced sweetening can be partially reversed by temperature reconditioning [37]. Since cold is also an abiotic stress; as an adaptive behavior of tubers to cold stress, it can induce enhanced starch-sugar metabolism and cause sugar accumulation [38]. The contents and basal metabolism of small-molecule metabolites such as sugars and free amino acids directly affect tuber adaptability to cold.…”
Section: Storage At Low Temperaturementioning
confidence: 99%
“…In a recent study, cold storage significantly affected certain metabolites like sugars, sugar alcohols, amino acids, and organic acids [43]. Based on this, it has been indicated that metabolites such as glucose, fructose, sucrose, asparagine, glutamine, citrate, malate, proline, and 4-aminobutyrate can be potentially utilized for the selection and development of potato cultivars for long-term storage, nutritional, and processing attributes [37][38][39][40]43].…”
Section: Storage At Low Temperaturementioning
confidence: 99%